2001
DOI: 10.1097/00003643-200106000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological control of opioid-induced pruritus: a quantitative systematic review of randomized trials

Abstract: Background and objective Numerous drugs have been used to prevent or to treat opioid-induced pruritus in the surgical setting. Their relative efficacy is not well understood. Methods The methods employed involved the systematic search (MEDLINE, EMBASE, Cochrane library, bibliographies, without language restriction, up to June 2000) for full reports of randomized comparisons of any intervention which is thought to be anti-pruritic (active) compared with placebo or no treatment (control) in surgical (including l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
0
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 60 publications
2
63
0
9
Order By: Relevance
“…Thus, newborn infants showed no signs of fetal distress. Our results were similar to those described in the literature, proving that the drug combination is safe in the doses used 7,9,19,21,28 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, newborn infants showed no signs of fetal distress. Our results were similar to those described in the literature, proving that the drug combination is safe in the doses used 7,9,19,21,28 .…”
Section: Discussionsupporting
confidence: 91%
“…Although the occurrence of nausea and vomiting during cesarean section is considered relevant, and frequently related to uterine exteriorization and peritoneal exposure, it has been currently described that opioids given intrathecally may confer protection against such adverse effects 9 . In a systematic review, Dahl et al 28 reported that the incidence of nausea and vomiting did not increase with the use of fentanyl and sufentanil, in agreement with findings by other authors 1,26 . Those authors described that antiemetic agents were required only in groups where the local anesthetic was used alone.…”
Section: Discussionsupporting
confidence: 78%
“…27 In our study, three patients complained of itching; in one case it caused enough discomfort to require interruption of the infusion. The association with midazolam could decrease the incidence of itching during remifentanil sedation; 28 in other cases droperidol could be useful.…”
Section: Discussionmentioning
confidence: 52%
“…The association with midazolam could decrease the incidence of itching during remifentanil sedation; 28 in other cases droperidol could be useful. 27 Remifentanil's prompt elimination can stop itching in patients who do not respond to pharmacological therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There were two earlier systematic reviews 34,35 on the pharmacological intervention of opioid-induced pruritus, but both did not focus on butorphanol and studies of pediatric patients were excluded. In our systematic review, four trials in children were available, and the combined data from three trials reporting the occurrence of pruritus showed that butorphanol could significantly reduce morphine-induced pruritus.…”
Section: Discussionmentioning
confidence: 99%